2001
DOI: 10.1103/physrevlett.86.2162
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Computing of Quantum Chaos and Imperfection Effects

Abstract: We study numerically the imperfection effects in the quantum computing of the kicked rotator model in the regime of quantum chaos. It is shown that there are two types of physical characteristics: for one of them the quantum computation errors grow exponentially with the number of qubits in the computer while for the other the growth is polynomial. Certain similarity between classical and quantum computing errors is also discussed.PACS numbers: 05.45. Mt, 03.67.Lx, 24.10.Cn A great interest to quantum compu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
43
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 32 publications
6
43
1
Order By: Relevance
“…Grover's algorithm [12] was studied in [13] with the help of a phenomenological model of probability diffusion, but the dependence of the model parameters on the number of qubits and ǫ was not determined. Conclusions similar to those in [7] were reached also in [14], where again the test algorithm was Grover's one 1 , and in a number of articles about the simulation of quantum chaotic maps [9,15,16,17,18]. These results show that the timescale for the degradation of the fidelity of a q.c.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Grover's algorithm [12] was studied in [13] with the help of a phenomenological model of probability diffusion, but the dependence of the model parameters on the number of qubits and ǫ was not determined. Conclusions similar to those in [7] were reached also in [14], where again the test algorithm was Grover's one 1 , and in a number of articles about the simulation of quantum chaotic maps [9,15,16,17,18]. These results show that the timescale for the degradation of the fidelity of a q.c.…”
Section: Introductionsupporting
confidence: 56%
“…Although there are other quantities which are exponentially sensitive to the number of qubits [15,18,19]. 3 Satisfying this condition corresponds to tuning the gate implementation in order to eliminate the systematic part of the error.…”
Section: Introductionmentioning
confidence: 99%
“…Here n q can be viewed as the number of qubits (two-level quantum systems) of which a quantum computer is built. Apart from Shor's algorithm, the QFT finds a number of various applications in quantum computation, including the simulation of quantum chaos models showing rich and complex dynamics [5,6,7]. The sensitivity of the QFT to imperfections was tested in numerical simulations and the time-scales for reliable computation of the algorithm were established [6,7,8,9].…”
mentioning
confidence: 99%
“…Apart from Shor's algorithm, the QFT finds a number of various applications in quantum computation, including the simulation of quantum chaos models showing rich and complex dynamics [5,6,7]. The sensitivity of the QFT to imperfections was tested in numerical simulations and the time-scales for reliable computation of the algorithm were established [6,7,8,9].A few years after the discovery of the QFT algorithm, it has been shown that certain WT can also be implemented on a quantum computer in a polynomial number of quantum gates [10,11,12]. In fact, explicit quantum circuits were developed for the most popular discrete WT, namely the 4-coefficient Daubechies WT (D (4) ) and the Haar WT, both for pyramidal and packet algorithms [10,11,12].…”
mentioning
confidence: 99%
“…Furthermore, we emphasize that the quantum computation of quantities like dynamical localization or fidelity is a demanding testing ground for quantum computers. In the first case, we want to simulate dynamical localization, a purely quantum phenomena which is quite fragile in the presence of noise [30,31]; in the latter case, fidelity is computed as a result of a sophisticated many-qubit Ramsey-type interference experiment. Therefore the computation of these quantities appears to be a relevant test for quantum processors operating in the presence of decoherence and imperfection effects.…”
Section: Discussionmentioning
confidence: 99%